Growth hormone gene polymorphism in boer goat - Malaswamy, Magamaee (2016)
In meat goat industry, growth traits of goat are of primary concern during breeding due to its economic determinant value. Molecular genetic information may be applied with quantitative genetics approach to select parental stocks of high merit to be used in breeding programmers to achieve rapid genetic improvement of herds. The growth hormone (GH) gene plays an important role in the regulation of growth and enhancement of amino acid incorporation into muscle protein. Polymorphism of the GH gene and its association with birth chest girth and weaning weight has been reported. The objective of this study was to investigate the GH gene polymorphism in a Boer goat herd in Malaysia using restriction fragment length polymorphism (RFLP). DNA extracted from blood samples of 30 randomly selected Boer goats were amplified for a partial region of the GH gene using specific primers. The polymerase chain reaction (PCR) products were electrophoretically separated in 2% agarose gel for confirmation of amplification success. The PCR amplicons were then digested using the HaeIII restriction enzyme. The RFLP products were subjected to electrophoresis using 2% agarose gel and the genotypes identified. The PCR amplified product for the partial region of the GH gene was approximately 422 bp (base pair). Two genotypes were identified for the GH locus in the Boer goat population – AA and AB. The AA genotype showed two bands of approximately 366 bp and 56 bp. The AB genotype showed three bands which were approximately 422 bp, 366 bp and 56 bp. The frequency of the AB genotype was 0.9, while the frequency of the AA genotype was 0.1. The BB genotype was absent among the animals studied. Allele A was of higher frequency (0.55) compared to allele B (0.45). The population was not in Hardy-Weinberg equilibrium (HWE) for this locus (P<0.05). The herd exhibited heterozygosity excess. The Boer goat herd studied showed higher frequency of the AB genotype which has been reported to be associated with better growth performance than the other genotypes. This may be the result of the initial improvement strategies adopted during the development of the Boer goat. The deviation of the locus from HWE may be attributed to the selection and mating practices in the Boer goat herd studied. Future studies should include more Boer herds and investigate other regions of the GH gene. In addition, association analysis with growth traits should be conducted so that the molecular markers to be incorporated into the selection programmers may be identified and validated.